Production and Identification of Nano-Sized Iron Oxide for Ecological Applications - WANG JUN , WANG JUN; DR. AIMAN AL-ODAINI, DR. AIMAN AL-ODAINI; DR MOHAMMED SALEH NUSARI , DR MOHAMMED SALEH NUSARI (International Journal of Multidisciplinary Research and Studies, 2024)
Synthesis of Nanomaterials: "In other words, this is a top-down approach. Through this method, nanoparticles having magnetic and catalytic capabilities have been fabricated. Ball milling and subsequent annealing are simple ways for producing vast amounts of varied Nano powders. Atomic-level alloying is accomplished by the milling of elemental blends, pre-alloyed powders, and ceramics. Put four balls made of hardened steel in a stainless steel container with some graphite powder. The "Argon gas is used to purge the container (Shah and Ahmad, 2010). The pieces are annealed at 1400°C in a vacuum after undergoing extensive grinding. There has been no breakthrough in understanding the mechanism behind this procedure. According to this idea, mechanical alloying involves a process in which "Ball impacts repeatedly shatter an alloy and then cause it to consolidate at the impact site. Manufacturing Mg2Ni since then has included a solid-state mechanical alloying technique using powdered components (Iturbe-Garca et al, 2010). Nanoscale materials have garnered a lot of interest because to the fact that their unusual physical properties set them apart significantly from their more common coarser equivalents (Mandal et al., 2008, Deb et al., 2001). These micro-sized items are larger than atoms and molecules but much smaller than solid blocks. Just because "because they violate the laws and principles of absolute quantum chemistry and classical physics. Nano-phase and nanostructure materials are essential building blocks in many fields, including electronics, due to their ultra-small dimensions, large surface areas, useful interfacial defects, and interface-dominated nature "as well as in the fields of optics, pharma, paint, coating, superconductors, semiconductors, and catalysis. Dye and pigment consumption has increased dramatically in recent years (Dong et al., 2011, Zhou et al., 2010). Dye waste is a well-known environmental pollutant, and some of it is toxic or even carcinogenic (Wang et al., 2005, Zhu et al., 2012). These colours are very apparent in water even at very low concentrations and should be avoided (Hu et al., 2010). Chromophores are what give a molecule its colour, while auxochromes are what make it more water-soluble and increase its affinity "these two elements are the primary reason why molecules of colour may exist (Gupta et al., 2009)